PENGARUH BEBAN KERJA, LINGKUNGAN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN DI BPR PERUMDA MAJALENGKA - Herawati, Fuji; Fauzan, Hemmy; Suhendra (JEBI | Jurnal Ekonomi Bisnis Indonesia, 2024)
The research sample was determined using purposive sampling involving 95 respondents. We used multiple linear regression to analyse all the data in this study. The results showed that it's not just one thing that affects performance. It's a combination of things: the workload, the work environment and job satisfaction. We also found that workload, work environment and job satisfaction all have a significant impact on employee performance (p=0.000). It would be great if Perumda BPR Majalengka Bank could create a safe and comfortable environment for their employees and provide tasks and responsibilities that match their abilities and skills.